3-D Numerical Study of CFB 110 MW: Fluidization in Furnace and Cyclone with Loads And Air Combustion Variation - Wirahadi, Ari; Mirmanto, Heru (IPTEK The Journal for Technology and Science, 2025)
Circulating Fluidized Bed (CFB) Boiler has advantages when uses low rank coal compared to Pulverized Boiler. It will be less operational cost but it has greater risk in degradation because of sands material inside the process. Air combustion between primary air and secondary air is one importance parameter that influence fluidization of CFB. Numerical simulation of commercial CFD was used with Eulerian multiphase model implemented to analyzed sand volume of fraction, air and sand velocity including distribution of pressure around furnace. It was used 55%-45% air combustion ratio of primary and secondary air as reference when boiler operated at 63% and 100% based on operation performance of CFB and then it was simulated with additional variation of air combustion ratio with 50%-50%. Simulation of 110% load was added using all of variation of air combustion. The simulation showed that fluidization with air combustion ratio 50%-50% and 55%-45% executed well when operated at 63%. Meanwhile, fluidization 100% and 110% with all those air combustion ratios would cause a great number of sands entered inlet cyclone and higher sands and air velocities.